The Impact of Assets Disposal and Economic Crisis on the Valuation of Asset Write-offs (Journal of Business Management and Accounting, 2011)
The financial crisis that occurred in Malaysia in the last decade followed by a series of corporate restructuring exercises trigger some fi rms to write off assets value. The incentives to write off may come from signalling future distress, current restructuring exercises,  or  taking  the  opportunity  to  blame  the  crisis.  This  scenario  creates  an  opportunity  to  investigate  the  market  reaction  on  different  causes  of  asset  write-off  during  a  crisis  period  which  is  not  found  in  prior  studies.  This  paper  examines  the  effect of specifi c events such as asset disposal and economic crisis on the valuation of asset  write-offs.  Asset  write-offs  related  to  disposal  of  assets  (likely  to  be  associated  with streamlining business activities) and economic crisis (a factor beyond the control of the fi rm) are expected to receive less negative impact from the market compared to write-off events not associated with a disposal or crisis. The data consists of listed non-fi nancial fi rms on Bursa Malaysia (3,301 fi rm-years) from fi nancial year 1990 to 2000. A  multivariate  regression  model  is  used  to  test  the  prediction.  We  fi  nd  results  which  are not consistent with the predictions. One possible reason that can explain the results is  that  the  market  interprets  asset  write-offs  to  be  associated  with  big-bath  activities  which subsequently would result in more discounts attached to such write-off.